Weapons or deterrents? Nudibranch molluscs use distinct ecological modes of chemical defence against predators. Issue 4 (9th December 2021) - Winters, Anne E.; Chan, Weili; White, Andrew M.; van den Berg, Cedric P.; Garson, Mary J.; Cheney, Karen L.
Abstract: Defensive chemicals are used by plants and animals to reduce the risk of predation through different mechanisms, including toxins that cause injury and harm (weapons) and unpalatable or odiferous compounds that prevent attacks (deterrents). However, whether effective defences are both toxins and deterrents, or work in just one modality is often unclear. In this study, our primary aim was to determine whether defensive compounds stored by nudibranch molluscs acted as weapons (in terms of being toxic), deterrents (in terms of being distasteful) or both. Our secondary aim was to investigate the response of different taxa to these defensive compounds. To do this, we identified secondary metabolites in 30 species of nudibranch molluscs and investigated their deterrent properties using antifeedant assays with three taxa: rock pool shrimp, Palaemon serenus, and two fish species: triggerfish Rhinecanthus aculeatus and toadfish Tetractenos hamiltoni . We compared these results to toxicity assays using brine shrimp Artemia sp. and previously published toxicity data with a damselfish Chromis viridis . Overall, we found no clear relationship between palatability and toxicity, but instead classified defensive compounds into the following categories: Class I & II—highly unpalatable and highly toxic; Class I—weakly unpalatable and highly toxic; Class II—highly unpalatable but weakly toxic; WR (weak response)—weakly unpalatable and weakly toxic. We also found eight extracts from six species that did not display activity in any assays indicating they may have very limited chemical defensive mechanisms (NR, no response). We found that the different classes of secondary metabolites were similarly unpalatable to fish and shrimp, except extracts from Phyllidiidae nudibranchs (isonitriles) that were highly unpalatable to shrimp but weakly unpalatable to fish. Our results pave the way towards better understanding how animal chemical defences work against a variety of predators. We highlight the need to disentangle weapons and deterrents in future work on anti‐predator defences to better understand the foraging decisions faced by predators, the resultant selection pressures imposed on prey and the evolution of different anti‐predator strategies. Abstract : The authors identified secondary metabolites in 30 species of nudibranch molluscs and using assays with different taxa found no clear relationship between palatability and toxicity. The results improve our understanding of how animal chemical defences work against predators and highlight the need to disentangle weapons and deterrents in future work.